Caracterização morfoagronômica e molecular da coleção de germoplasma de sisal da Embrapa Algodão - Souza, Silmara Chaves de (2017)
Knowledge of the genetic diversity available in the sisal germplasm collection is essential for breeding programs, so it is imperative to obtain as much information as the characteristics related to the species. Morphoagronomic and molecular data when analyzed mainly together are determinants for studies of genetic divergence between accessions. The objective of this study was to evaluate the genetic divergence present in the Agave accessions of the Embrapa Cotton Germplasm Active Collection by means of morphoagronomic and molecular data. Thirty-seven Agave accessions were kept in the experimental field in Monteiro-PB and the following characteristics were evaluated: leaf number (NFO), plant height (ALT), leaf length (CFO), leaf weight , Dry weight (PFIF), dry fiber weight (PFIS), fiber length (CFI), presence of border spikes (PEB), tillering (PF) and resistance to folding (DR). Ten ISSR (Inter Sample Sequence Repeat) oligonucleotides were used for molecular analyzes. The data were interpreted as qualiquantitative for the morphoagronomic and qualitative binary characters for the molecular markers. The agronomic data were submitted to analysis of variance and the means comparison was done by the Scott-Knott test at 5% probability. The dissimilarity measurements were obtained by Gower distance for the morphoagronomic data and by the Jaccard coefficient for the molecular data. The sum of the matrices of dissimilarity of the morphoagronomic and molecular data was made; and the grouping was done by the hierarchical UPGMA method and Tocher optimization. The agronomic characteristics presented high genetic variability among the sisal accessions. IAC accesses were the ones that presented the least distance between them, indicating a possible narrow genetic base and high degree of kinship. Hybrids Kenya and RN as the most similar accesses and the access Tatuí 2 the most divergent, being indicated for possible crossings. The results obtained in this study will support the crop improvement program, which may allow the appearance of superior materials.